2005
DOI: 10.1111/j.1365-2729.2005.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning with a mobile game: design and motivational effects

Abstract: Mobile technologies offer the opportunity to embed learning in a natural environment. This paper describes the design of the MobileGame prototype, exploring the opportunities to support learning through an orientation game in a university setting. The paper first introduces the scenario and then describes the general architecture of the prototype. The main part of the paper focuses on the evaluation of design issues and the effects observed in two trials. Design issues include: Supporting work on the move pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(144 citation statements)
references
References 20 publications
8
129
0
7
Order By: Relevance
“…Learners are attentive (Wijers, Jonker, & Drijvers, 2010). Students are mentally ready for learning (Schwabe & Göth, 2005). Players immerse themselves in the game (Carrigy, Naliuka, & Haahr, 2010).…”
Section: Learning Outcomes Patterns and Ar Taxonomiesmentioning
confidence: 99%
“…Learners are attentive (Wijers, Jonker, & Drijvers, 2010). Students are mentally ready for learning (Schwabe & Göth, 2005). Players immerse themselves in the game (Carrigy, Naliuka, & Haahr, 2010).…”
Section: Learning Outcomes Patterns and Ar Taxonomiesmentioning
confidence: 99%
“…Bhaskar and Govindarajulu, 2010;Naismith et al, 2005;Schwabe and Goth, 2005). This complements earlier findings from studies of distance learning which showed that students like being informed by the voice of their educator, listening to interviews or debates, hearing from experts and being encouraged with a reassuring audio message (Durbridge, 1984).…”
Section: Introductionsupporting
confidence: 74%
“…The review identified patterns within mobile learning games that positively influence motivation and knowledge gain. With regard to 'hard learning' [25], empirical evidence is fragmented though, e.g. the diverse studies had different statistical bases (dependent/independent variables) and different research methods applied.…”
Section: Discussion and Future Workmentioning
confidence: 99%